Stability in m-quota games - Bondareva, O. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:О. Н. Бондарева, Устойчивость в играх с m-квотойO. Bondareva, Stabilumas lošimuose su m-kvota